Hypothesis on the role of cholesterol crystals in spontaneously ruptured aortic plaques: Potential triggers for inflammation and systemic effects - Chikao Yutani; Hirotaka Noda; Nobuzo Iwa; Sei Komatsu; Satoru Takahashi; Yoshiharu Higuchi; Kazuhisa Kodama (American Heart Journal Plus)
Cholesterol crystals (CCs) are a key component of atherosclerotic plaques and play a pivotal role in plaque progression, rupture, and the resulting inflammatory responses. CCs emboli trigger proinflammatory cytokines which can potentially lead to organ damage. Spontaneously ruptured aortic plaques (SRAPs) are frequently observed via non-obstructive general angioscopy (NOGA) in patients with or suspected coronary artery disease. The release of CCs from SRAPs can activate the innate immune system and induce neutrophil extracellular trap (NET) formation, further exacerbating inflammation. Inflammation levels in SRAPs vary, and the interleukin (IL)-6 ratio may reflect the degree of inflammation. Systemic inflammation induced by CCs may contribute to conditions that may lead to cerebral infarction, and chronic kidney disease. The effects of anti-inflammatory drugs, including IL-6 inhibitors, IL-1β inhibitors, and colchicine, may be evaluated by measuring the IL-6 ratio in SRAPs. This review examined innate immunity mechanisms associated with CCs in SRAPs sampled via NOGA and discussed their systemic impact and potential therapeutic strategies.